High-pressure fluid shunting device - LI CAOXIONG; SHI JINGJING; LIAO JIAPING; HAO QIANG; XIAN CHENGGANG; ZHANG MUYANG (2022)
The utility model relates to a high-pressure fluid shunting device, which is characterized in that a water inlet is positioned at the upper part, fluid is separated by a branch flow channel after entering the water inlet, a bypass flow channel is arranged on the side surface of the branch flow channel, the upper flow channel of the bypass flow channel is arc-shaped, and the lower flow channel of the bypass flow channel is a straight channel. The included angle between the upper runner and the center line of the branch runner is an acute angle, the included angle between the lower runner and the center line of the branch runner is an acute angle, a piston is arranged on the lower portion of the junction of the lower portion of the bypass runner and the branch runner, the piston can be controlled by a power system to move in the axial direction of the piston, and then the communication state of the bypass runner is controlled. The water outlets are located in the lower portion, fluid can flow through the multip